2012
DOI: 10.1089/scd.2011.0041
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem/Progenitor Cells Express Functional Mitochondrial Energy-Dependent Cystic Fibrosis Transmembrane Conductance Regulator

Abstract: Bone marrow-derived hematopoietic stem/progenitor cells (HSPCs) encompass a wide array of cell subsets with different capacities of engraftment and injured tissue-regenerating potential. The characterization/ isolation of the stem cell subpopulations represents a major challenge to improve the efficacy of transplantation protocols used in regenerative medicine. Cystic fibrosis (CF) is one of the diseases whose hope of cure relies on the successful application of cell-based gene therapy. This study was aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 68 publications
4
20
0
Order By: Relevance
“…We have previously shown that the Sca-1 + population in naïve mice is comprised of two subpopulations, one smaller and one bigger, according to their physical parameters [23]. These two subsets were further analyzed for CD49d expression in the context of LPS-induced inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the Sca-1 + population in naïve mice is comprised of two subpopulations, one smaller and one bigger, according to their physical parameters [23]. These two subsets were further analyzed for CD49d expression in the context of LPS-induced inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that resident HSPCs are comprised of two subsets as determined by physical parameters and mitochondrial content [23]. R1 (bigger) cells are less primitive in that they display higher levels of mitochondria, as also shown in human CD34 + cells [56].…”
Section: Discussionmentioning
confidence: 99%
“…Even in functionally identified stem cell populations, cellular and molecular properties and behavior vary [Lemischka et al, 1986;Dykstra et al, 2007]. We [Piro et al, 2012;Trotta et al, 2013] and others [Kucia et al, 2008;Wong et al, 2009;Ratajczak et al, 2011] have identified HSPC subpopulations on the basis of immunophenotyping. It is not known whether these subpopulations are endowed with different engraftment capacity in the lung, although recent work points to this possibility [Wong et al, 2009].…”
Section: Heterogeneity Of Hspcs and Mscsmentioning
confidence: 96%
“…types, including hematopoietic stem cells 15,16 and differentiated cells ensuing from them. 17 Of note, CFTR protein expression on neutrophil membranes, secretory vesicles, and phagocytic vacuoles, 18,19 and in MNC 20,21 and macrophages 22 has been described.…”
Section: Besides Epithelial Cells Cftr Expression Has Been Shown In mentioning
confidence: 99%
“…Besides epithelial cells, CFTR expression has been shown in other cell types, including hematopoietic stem cells and differentiated cells ensuing from them and in MNC and macrophages has been described.…”
Section: Introductionmentioning
confidence: 99%